2000
DOI: 10.1074/jbc.m001278200
|View full text |Cite
|
Sign up to set email alerts
|

Cysteines Involved in Radical Generation and Catalysis of Class III Anaerobic Ribonucleotide Reductase

Abstract: Class III ribonucleotide reductase (RNR) is an anaerobic glycyl radical enzyme that catalyzes the reduction of ribonucleotides to deoxyribonucleotides. We have investigated the importance in the reaction mechanism of nine conserved cysteine residues in class III RNR from bacteriophage T4. By using site-directed mutagenesis, we show that two of the cysteines, Cys-79 and Cys-290, are directly involved in the reaction mechanism. Based on the positioning of these two residues in the active site region of the known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 42 publications
(43 reference statements)
4
28
0
Order By: Relevance
“…In this paper we further investigate the role of the equivalent cysteine residues of the C terminus of E. coli protein ␣ with the help of original site-directed mutants, and confirm that they are critical for glycyl radical formation (5). The E. coli system has the advantage over the bacteriophage one in that it allows pure preparations of the ␤ activase and thus more accurate characterization of the radical generation reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we further investigate the role of the equivalent cysteine residues of the C terminus of E. coli protein ␣ with the help of original site-directed mutants, and confirm that they are critical for glycyl radical formation (5). The E. coli system has the advantage over the bacteriophage one in that it allows pure preparations of the ␤ activase and thus more accurate characterization of the radical generation reaction.…”
mentioning
confidence: 99%
“…1), at the C-terminal end of protein ␣ (11). Mutation of any of these cysteines (Cys-543, Cys-546, Cys-561, or Cys-564) to serine in RNR from bacteriophage T4 eliminated production of the glycyl radical, as indirectly shown from the absence of cleavage of the ␣ polypeptide at the radical site during exposure to air (5). In the initial 3D structure of the enzyme from bacteriophage T4, these cysteines were shown to belong to a portion of the C-terminal region of the polypeptide, between the end of the last ␤-strand of the ␣Ϫ␤ barrel and the loop containing the glycyl radical residue (residues 543-570) that was disordered in the crystal (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In class III RNR, alignments of the 20 nrdD sequences presently available have revealed, among the 15-20 Cys generally present, the occurrence of five invariants, one highly conserved and three moderately conserved cysteine residues (18). Site-directed mutagenesis studies done on the enzyme from the bacteriophage T4 have demonstrated that two of these invariants are directly involved in the turnover of the reaction in agreement with the presence of two cysteines in the substrate site observed in the three-dimensional structure of the protein (12,19). The three other invariants are part of a CXXCX 14 CXXC motif (not visible in the three-dimensional structure) located in the C terminus of the polypeptide.…”
Section: Discussionmentioning
confidence: 49%
“…The three other invariants are part of a CXXCX 14 CXXC motif (not visible in the three-dimensional structure) located in the C terminus of the polypeptide. Each of these cysteines was essential for the formation of Gly ⅐ and was thus proposed to participate to radical transfer reactions during enzyme activation (19).…”
Section: Discussionmentioning
confidence: 99%